A STUDY TO EXPLORE PREFERRED METHOD OF TREATMENT AMONG PHYSIOTHERAPISTS FOR MECHANICAL LOW BACK PAIN (International Journal of Physiotherapy, 2016)
Background: Conservative treatment remains the standard of care for treating nonspecific mechanical low back pain which is very common problem all around the world. In Pakistan, physiotherapists encounter this problem frequently in clinical practice. Despite a wide variety of treatments, 100 percent results have been unachievable. The purpose of this study was to establish a Standard and Uniform Physiotherapy Protocol for mechanical low back pain.Methods: To achieve the objective of this study, a questionnaire with structured and open ended questions were designed and distributed to hospitals and private clinics. 139 questionnaires were distributed from 1st March 2009 to 30th May 2009. By the end of July 5, 2009, 101 were filled and returned. The data was analyzed using descriptive statistics.Results: Results have shown that McKenzie (25%), combination of McKenzie and Maitland (9%) were among the preferred techniques. However, 14% did not use a specific technique. The preferred physical agents were hot packs (22%), combination of hot packs, ultrasound, TENS (22%). However, 4% did not prefer any physical agent. Out of 101 subjects per week, 20 subjects were treated for 7 days, 11 were treated for 5 days, 53 were treated for 3 days, 6 were treated for 2 days and 11 were treated for 1 day. The recurrence rate was 32.14% for those who were treated for six days, 34.75% for those treated for 5 days, 33.55% for those who were treated for 3 days, 31.25% for those who were treated for 2 days, and 37.55% for those who were treated for one day. 39% did not consider ergonomical issues while 27% did not advice regarding the patient nutritional facts. Average depression among patients was 24.7%.Conclusion: This study shows that the results for mechanical low back pain were not as effective with combination of techniques and modalities. If the physiotherapists had taken the psychological factors, ergonomical approach and nutrition into consideration, the results would have improved to a significant level.